SOURCES OF FINANCING RUSSIAN ECONOMY GROWTH - Vladimir A. Slepov; Vladimir K. Burlachkov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article identifies key sources of shaping investment potential of the economic system, which can activate corresponding multiplier: non-distributed profit, investment of consolidated budget, resources of credit system and stock exchange, household savings. The authors show positive dynamics of resource volume changes, which are available for economic growth financing in Russia, in 2012-2015 that stands in negative correlation with GDP changes during the mentioned period. The article identifies and analyzes factors preventing from getting the necessary effect from the given sources. The authors put forward the optimization model identifying conditions of maximizing finance resources of developing the economic system to attain GDP growth.